A bacterial biosensor encoding a genetically modified LuxR receptor exhibits improved detection of Pseudomonas aeruginosa's biomarker molecule 2-aminoacetophenone. Issue 66 (1st August 2018) - Kviatkovski, I.; Yarnitzky, T.; Shushan, S.; Schwartz-Harari, O.; Nir-Paz, R.; Helman, Y.
Abstract : A modified LuxR-M22 receptor (B) exhibits an improved affinity towards 2-aminoacetophenone (2-AA) relative to the native LuxR receptor (B). Abstract : 2-Aminoacetophneone (2-AA) is a volatile molecule produced in high amounts by the opportunistic pathogen Pseudomonas aeruginosa . We have previously shown that 2-AA activates the quorum sensing (QS) LuxR receptor of Aliivibrio fischeri . In the present study we were able to improve LuxR's affinity and detection limit for 2-AA by genetic modification of three amino acids within the binding pocket of the receptor. Expression of the modified LuxR receptor in a luminescent bacterial biosensor provided an efficient detection assay of 2-AA in clinical P. aeruginosa strains isolated from blood and lung infections, as well as in phlegm samples obtained from subjects suffering from lung infections.